2012
DOI: 10.1063/1.4757568
|View full text |Cite
|
Sign up to set email alerts
|

Communication: On the isotope anomaly of nuclear quadrupole coupling in molecules

Abstract: The dependence of the nuclear quadrupole coupling constants (NQCC) on the interaction between electrons and a nucleus of finite size is theoretically analyzed. A deviation of the ratio of the NQCCs obtained from two different isotopomers of a molecule from the ratio of the corresponding bare nuclear electric quadrupole moments, known as quadrupole anomaly, is interpreted in terms of the logarithmic derivatives of the electric field gradient at the nuclear site with respect to the nuclear charge radius. Quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…, νQ(I1)νQ(I2)=QI1QI2(1+1scriptVccscriptVccR|R = RI2ΔR12)+O(ΔR122) where RI2 is the charge radius of the isotope I 2 and ΔR12 is the variation of the charge radius between isotopes I 1 and I 2 . Calculating the logarithmic derivative of the principal EFG value in a series of gold compounds, FZC found that the nuclear quadrupole anomaly 195ΔAu197 can reach values up to 0.2% according to NESC/CCSD calculations. An anomaly of such a magnitude should be reflected by measured NQCC, as the accuracy of current techniques in microwave spectroscopy is sufficient to detect an anomaly predicted for the 79195Au, 79197Au pair of isotopes …”
Section: Nesc Analytic Energy Derivativesmentioning
confidence: 99%
“…, νQ(I1)νQ(I2)=QI1QI2(1+1scriptVccscriptVccR|R = RI2ΔR12)+O(ΔR122) where RI2 is the charge radius of the isotope I 2 and ΔR12 is the variation of the charge radius between isotopes I 1 and I 2 . Calculating the logarithmic derivative of the principal EFG value in a series of gold compounds, FZC found that the nuclear quadrupole anomaly 195ΔAu197 can reach values up to 0.2% according to NESC/CCSD calculations. An anomaly of such a magnitude should be reflected by measured NQCC, as the accuracy of current techniques in microwave spectroscopy is sufficient to detect an anomaly predicted for the 79195Au, 79197Au pair of isotopes …”
Section: Nesc Analytic Energy Derivativesmentioning
confidence: 99%
“…Analytic second derivatives have also been explored in the computation of nuclear Hessians as well as NMR chemical shieldings . Initial applications of SFX2C‐1e energy derivatives in the calculation of the properties of heavy‐element compounds have turned out promising . A more detailed discussion of analytic SFX2C‐1e energy derivatives is presented in the following.…”
Section: State‐of‐the‐art Analytic Derivative Theory In Relativistic mentioning
confidence: 99%
“…8 As for the calculation of second order response properties, we developed the methodology for the analytic calculation of vibrational frequencies, 3,9 static electric polarizabilities, or infrared intensities 3 utilizing the 1c-NESC method. We applied these methods to predict molecular properties of mercury, 10 gold, 11 uranium containing molecules, 3 or other relativistic molecules. 12 In view of the importance of spin-orbit coupling (SOC) for atomic and molecular properties, [13][14][15][16][17][18][19][20][21] we extended, in another project, the 1c-NESC approach to a 2c-NESC method that reliably predicts the effects of SOC on the relative energies of relativistic systems.…”
Section: Introductionmentioning
confidence: 99%